2019
DOI: 10.5951/mathteacmiddscho.24.6.0362
|View full text |Cite
|
Sign up to set email alerts
|

Number Talks for Statistics and Probability

Abstract: Short, mathematical discussions can elicit students' reasoning and focus on foundational ideas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They suggested number talks that present images can launch discourse of multiple mathematical ideas among students. Gerstenschlager and Strayer (2019) provided strategies for implementing what they coined "statistical number talks" in middle school mathematics classroom (p. 363) and suggested number talks allow for teachers to evaluate prior knowledge as well as serve as an option for formative assessment.…”
Section: Research On Number Talksmentioning
confidence: 99%
“…They suggested number talks that present images can launch discourse of multiple mathematical ideas among students. Gerstenschlager and Strayer (2019) provided strategies for implementing what they coined "statistical number talks" in middle school mathematics classroom (p. 363) and suggested number talks allow for teachers to evaluate prior knowledge as well as serve as an option for formative assessment.…”
Section: Research On Number Talksmentioning
confidence: 99%
“…In their study in an urban third–grade classroom with a large EL population, Hufferd–Ackels et al (2004) demonstrated that a math–talk learning community can be developed and that mathematical understanding can be built through that community around math talks. Number talks have been defined as “short, mathematical, whole–class discussion during which students solve problems and share their ways of seeing and reasoning about mathematics” (Gerstenschlager & Strayer, 2019, p. 363). In elementary grades, number talks are often used as an instructional practice to encourage students to discuss and share ideas on how to solve computational problems beyond simply stating the procedure or rule (Parrish, 2011).…”
mentioning
confidence: 99%